Behavior related vocalizations of the Florida manatee (Trichechus manatus latirostris). Issue 3 (31st December 2021) - Brady, Beth; Moore, Jon; Love, Kim
Abstract: Florida manatees ( Trichechus manatus ) produce five broadly defined call types (squeaks, squeals, high squeaks, chirps, squeak‐squeals) but their use in social and nonsocial settings is unclear. The goal of this study was to investigate whether call categories and structure of manatee vocalizations varied with behavior. Multiple hydrophones were used to record vocalizations in four different environments and broad behavioral states. Vocalizations recorded from resting, cavorting, stressed, or feeding wild animals were subjected to mixed linear effects models to test whether vocalizations produced varied with behavior and calf presence. Measures of duration, entropy, and frequency modulation were extracted from vocalizations to investigate if structural parameters differ among behaviors. Although all five call categories were recorded, results suggest manatees vocalize using primarily three call types and vary the structure of the call based on behavior. High squeaks were correlated with calf presence. High entropy squeals were proportionally higher during cavorting suggesting they may be related to a heightened state of arousal. Squeaks were the dominant call type produced and were longer in duration and higher in frequency modulation when animals were stressed. This research provides a foundation for comparative studies on vocal behavior for the Florida manatee as well as studies on related species.